Optimalisasi Penjadwalan, Perawatan dan Perbaikan Pembangkit PLTD 20 kV dengan Levelized Reserve Method - Abraham Latumahina; Wijono Wijono; Hadi Suyono (Fakultas Teknik, Universitas Brawijaya, 2015)
The power system reliability is one of aspect in the power system operation. One factor influences the power system scheduling is system maintenance. Same method a used in the maintenance scheduling. i.e , GA (Genetic Algorithm) method, GSM (Generator Maintenance Scheduling) method, RBM (Risk-based maintenance) method, Annealing method and Levelized Reserve Method (LRM). LRM is used with the basis of balance of reserve capacity . LRM method is the divided two method, Levelized Reserve Capacty Method (LRCM) and Levelized Reserve Rate Method (LRRM). The mentenance scheduling optimisation in the riset includes two solution and five step. The best solution is proposed to be implemented in the maintenance scheduling of Region IX Maluku and North Maluku 20 Kv branch Ambon. Solution I stage 4 LRCM and solutions I stage 4 LRRM. The result of 22 generating units with capacity varying power unit, it can perform maintenance on 12 units. The balance of power throughout the duration of the reserve maintenance period can be met, namely to methods LRCM the results ranged 13.6 MW - 16.2 MW, while the result for the method LRRM range of 13.6 MW - 17.2 MW. The calculation of the initial backup highest power rating in accordance with the method Lrrm is 0.53% and the highest end of the reserve power of 0.39%.Index Terms — Optimization of scheduling , LRM, LRCM, LRRM.